THE ROLE OF REAL PROJECTS IN TEACHING DESIGN THINKING TO FUTURE PRIMARY SCHOOL TEACHERS - Mamadaminova Munisa Makhmudjon qizi (Bright Mind Publishing, 2026)
This article examines the essence of the design thinking concept in accordance with contemporary educational requirements, its role in pedagogical practice, and the theoretical and methodological foundations for developing this competency in future primary school teachers. The study analyzes an approach to understanding real educational problems and addressing them through the stages of design thinking. Although no experimental study was conducted, well-grounded conclusions are drawn based on scientific and theoretical evidence.
Keywords: Design thinking; project-based activity; school-related problems; primary education.